(3GdYhGed GdLOjOI aj GdfMhs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aGYde Cfg dGHO dcd WGdH eYQaI GdEYQGH ef eYQaI eGFI TjA SJhf efgG jSei YGedG hKdGKhf eYehdG hYTQI jSei YedGs
(3BNQgG (B:s
(3hEf de jXgQ hde jbOQ aj BNQg jSei eMdjG fMh JhcdfG Ydi ef dG jCJj GdNjQ EdG ef LgJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs